Pangolin-inspired untethered magnetic robot for on-demand biomedical heating applications - Ren Hao Soon; Zhen Yin; Metin Alp Dogan; Nihal Olcay Dogan; Mehmet Efe Tiryaki; Alp Can Karacakol; Asli Aydin; Pouria Esmaeili-Dokht; Metin Sitti (Nature Communications, 2023)
Abstract Untethered magnetic miniature soft robots capable of accessing hard-to-reach regions can enable safe, disruptive, and minimally invasive medical procedures. However, the soft body limits the integration of non-magnetic external stimuli sources on the robot, thereby restricting the functionalities of such robots. One such functionality is localised heat generation, which requires solid metallic materials for increased efficiency. Yet, using these materials compromises the compliance and safety of using soft robots. To overcome these competing requirements, we propose a pangolin-inspired bi-layered soft robot design. We show that the reported design achieves heating > 70 °C at large distances > 5 cm within a short period of time <30 s, allowing users to realise on-demand localised heating in tandem with shape-morphing capabilities. We demonstrate advanced robotic functionalities, such as selective cargo release, in situ demagnetisation, hyperthermia and mitigation of bleeding, on tissue phantoms and ex vivo tissues.